Surveying New Muralism in Italy:: Urban Art Interventions for the Regeneration of Turin’s Architectural Heritage - Caffio, Giovanni (Street Art & Urban Creativity, 2015)
The phenomenon of urban art is one of the forces shaping contemporary urban spaces. Historically fought as vandalism in its “writing” component (the “black sheep” of the urban actors performing in the contemporary city), urban art has recently become more appreciated as an artistic expression, especially when regarded as a stage in the historical evolution of muralism. As several examples worldwide have shown, in the context of urban renewal, urban art can set off positive dynamics. Focusing on the Italian scene, I recognize the importance of past Italian interventions realized both in big cities, such as Rome, Turin and Bologna, and in small cities, such as Grottaglie (Taranto), Gaeta (Latina), Catanzaro, and Dozza (Bologna). In addition, the growing number of urban art festivals and public interventions seems to voice the citizens’ will to take the streets back, particularly where institutions are unable to intervene effectively in the urban domain due to political short-sightedness or lack of financial resources. The first aim of this paper is to illustrate and analyze some collective projects and informal actions through which citizens, associations, and institutions have given added value to the urban space. I will focus particularly on Turin, which has become one of the most interesting and rich urban art territories, thanks to public projects such as Murarte, Picturin, Nizzart and B.Art: Arte in Barriera. This study offers insights on how, by way of artistic deeds and apparently “weak” transformation systems, urban art may take innovative action so as to regenerate the city’s architectural heritage. The second aim of this paper is to propose a methodology for architectural surveying techniques applied to urban art. isIn current critical analysis, as well as in the representation and documentation of this type of work, the fundamental importance of the physical, architectural and urban environment in which the work is placed is often overlooked, if not completely omitted. In acknowledgment of these limitations, this paper proposes a documentation methodology that respects both the values of the process and the work itself. In this regard, painted walls must be considered as inseparable from the space in which they are located, from the material substrate supporting them, and from the time conditions in which they were realized. The process of examination and documentation therefore requires observation in situ, new digital and traditional survey techniques, and a variety of representations at different scales; with a view to understanding the reasons that led to the selection of a particular place in the city, and the way in which artistic action arises in relation to the historical environment and the social and political system that influenced its creation.